Aplikasi Model Cooperative Learning Sebagai Upaya Meningkatkan Antusiasme, Keaktifan dan Kepuasan Peserta Serta Capaian Kompetensi Pembelajaran Pada Mata Kuliah Perencanaan Infrastruktur - Yashinta Kumala Dewi Sutopo; Venny Veronica Natalia (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2016)
For S1 students of the Regional and Urban Development Study Program (PWK) who are educated and trained as professional and quality spatial planning, knowledge and expertise in planning 10 types of regional and city infrastructure is very important and absolutely essential to master. This competency was originally obtained by 4th semester students in the Infrastructure Planning and Transportation Course. But based on the evaluation of learning that has been done since the last 4 semesters (2011/2012 to 2014/2015), the achievement of these competencies is still far from the expected target. Mainly in understanding the material, less than 5% of participants were able to fully understand the material in 10 types of infrastructure in full, the rest were only able to properly understand material 1 or several types only. This study aims to determine whether the application of the cooperative learning model student team learning type can increase participant understanding, while enhancing 2 other aspects of competency achievement, namely social skills and practical planning skills. In addition, this study also aims to determine whether the application of this learning model can increase the enthusiasm, activeness and satisfaction of participants in the learning process. The method used in this study is a literature review of the cooperative learning model student team learning type, the application of the stages of the model in class, and the observation of the process and assessment of learning outcomes. Along with improvements to the learning method, improvements were made to the main components of learning and the application of its improvement in the class under study.